STRATEGI MARKETING SYARIAH MELALUI MARKETPLACE LAZADA DALAM MENINGKATKAN PENJUALAN: (Studi Kasus Toko Aries Beauty Store Banyuwangi) - Lutfiatur Rofi’ah; Sofi Faiqotul Hikmah (Universitas KH. Mukhtar Syafaat, 2025)
The objectives of this study are To determine the Sharia Marketing Strategy at Aries Beauty Store. The data analiys technique used in this study is qualitative or descriptive data analysis.The result of this research is that Aries Beauty Store uses a marketing mix strategy (4p) including Product, Price, Place, and Promotion. In addition, it also uses sharia marketing strategis according to Kertajaya (2006) Rabbaniyah, Akhlaqiyah, Al-waqiiyah, and Al-insaniyah. There is a different in the theory af Al-waqiiyah that in theory there is no differentation, but Aries Beauty Store differentiates according to the target market according to the consumer’s budget. Research conucted in the field shows that store Aries Beauty Store uses the marketing mix theory in its marketing, namely Place, Price, Product, Promotion. For the marketing strategy of Sharia Shop Aries Beauty Store uses Shariah Marketing Strategy according to Kertajaya (2006) namely Rabbaniyah, Akhlaqiyah, Al-waqiiyah and Al-insaniyah. However, Al-waqiiyah has a difference between theory and field, so it can be concluded that the theory according to Kertajaya and the marketing strategy in the field does not match Al-waqiiyah theory.